Rut 3:9 en 4:5: Wat het die (leviraats) huwelik met lossing te doen? - Villiers, Gerda de (HTS teologiese studies, 2012)
Ruth 3:9 en 4:5: What does the levirate marriage have in common with the practice of land redemption? This article examines two passages in the book of Ruth – 3:9 and 4:5. Both pertain to two practices in ancient Israel, namely the levirate marriage and the redemption of property – here in the case of the book of Ruth. Ruth 3:9 hints only indirectly to these, therefore, I aim to indicate that Ruth does offer Boaz a marriage proposal and that some form of redemption of property is intended. In Ruth 4:5 these two practices are once again juxtaposed. Scholars propose various reasons why the levirate marriage and redemption are related to each other in the book of Ruth and nowhere else in the Hebrew Bible. It appears that their proposals can be related directly to their dating of the book, either pre- or post-exilic. In my article, I accept a post-exilic dating since the author of the book of Ruth seems to know most of the laws in the Pentateuch. I conclude with the views of Irmtraud Fischer, a feminist scholar who offers interesting perspectives from a feminist historical critical point of view.